Psychometric Properties of the Paykel Suicide Ideation Scale in a Secondary School in Colombia - Álvarez-Merlano, Nicolas (2024)
Objective. To determine discrimination, reliability and internal validity of the Paykel Suicidal Ideation Scale (PSS). Methods. Cross-sectional descriptive instrumental design. The sample consisted of 120 high school students enrolled in a public educational institution, who voluntarily answered the scale. Three evaluation stages were implemented. First: evaluation of sociodemographic statistics and item-total correlation. Second: evaluation of internal consistency using Cronbach's ordinal alpha and McDonald's ordinal omega. Third: construct validity by confirmatory factor analysis (CFA). Results. The final version has 5 items with a Cronbach's alpha of 0.90 (99% CI: 0.84-0.94) and McDonald's omega of 0.91 (99% CI: 0.86-0.94). The AFC validated the original Paykel model with a unidimensional internal structure with the following goodness-of-fit indicators: χ² = 8.35 (p = 0.14); gl = 5; χ²/gl = 1.67; CFI = 0.99; AGFI= 0.99; SRMR = 0.03 and RMSEA = 0.07. Conclusions. The scale is a useful instrument with satisfactory psychometric properties. It is recommended to evaluate suicidal ideation in high school students.